2024
DOI: 10.3390/antiox13030273
|View full text |Cite
|
Sign up to set email alerts
|

Nanoencapsulation of Maqui (Aristotelia chilensis) Extract in Chitosan–Tripolyphosphate and Chenopodin-Based Systems

Daniela Andrade,
Francisca Maldonado-Bravo,
Amador Alburquerque
et al.

Abstract: Maqui berries contain a high percentage of anthocyanins with high antioxidant and anti-inflammatory capacity but that are unstable in the colonic site. Nanocarriers based on polysaccharides and/or proteins can protect against the degradation of anthocyanins. The aim of this study was the nanoencapsulation of maqui extract (ME) in chitosan–tripolyphosphate (CTPP-ME), chenopodin (CH-ME), and chenopodin–alginate (CHA-ME). A standardised ME was prepared and then encapsulated in the nanosystems. The physicochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…This is evidenced by the low T50 values of F1Qt (8.5 h) compared to F4Qt (10.4 h) and P4Qt (12.9 h). Similar results were reported by Andrade et al [ 70 ] who used nanoencapsulation of a maqui extract in chitosan/tpp and QP nanovehicles to obtain a higher T50 (5.46 h) for the formulation with a strong intermolecular interaction with the encapsulated active ingredient. Additionally, it is reported that there is a greater release of Qt by diffusion at pH 5.4 compared to pH 7.4 from the NEs F4Qt and P4Qt.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…This is evidenced by the low T50 values of F1Qt (8.5 h) compared to F4Qt (10.4 h) and P4Qt (12.9 h). Similar results were reported by Andrade et al [ 70 ] who used nanoencapsulation of a maqui extract in chitosan/tpp and QP nanovehicles to obtain a higher T50 (5.46 h) for the formulation with a strong intermolecular interaction with the encapsulated active ingredient. Additionally, it is reported that there is a greater release of Qt by diffusion at pH 5.4 compared to pH 7.4 from the NEs F4Qt and P4Qt.…”
Section: Resultssupporting
confidence: 88%
“…The in vitro Qt dissolution of F4Qt, F5Qt, P4Qt, and P5Qt in PBS1X and Krebs buffer fits the Korsmeyer–Peppas model, capable of describing the release of drugs from polymers such as the QPA complex and QP, considering non-Fickian mechanisms [ 69 , 70 ]. See Table S3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation